Review: Effect of global warming on plant evolution and diversity; lessons from the past and its potential recurrence in the future - AHMAD DWI SETYAWAN (Smujo International, 2009)
Abstract. Setyawan AD. 2009. Effect of global warming on plant evolution and diversity; lessons from the past and its potential recurrence in the future. Nusantara Bioscience 1: 43-52. Lessons from the past show that global warming and glaciation are repeated natural cycles; the trigger factor is not always the same. Still, global warming is always accompanied by elevated levels of CO2 and greenhouse gases in the atmosphere, which causes the other rising global temperatures. Present and destruction of various plants and other living things continue to happen from time to time. Every era has its own life form, as a mirror of global environmental conditions at the time. Biodiversity is not always the same between one period of global warming and the subsequent global warming or one period of glaciation with the next glaciation. However, new breeds always show traces of the evolution of their ancestors. Man is one of the agents of global warming that began with developing agricultural systems since 8,000 years ago. The impact of climate change due to global warming should continue to be wary of. Based on past experience, global warming is always followed by mass extinctions, but various life forms will still survive even though their shape is almost certainly not the same as before. Living organisms that can survive will evolve into new taxa different from their parental taxa. Humans who were present at that time probably were not men present at this time, given Homo sapiens may have been extinct for not being able to adapt or otherwise has evolved into a new man who may no longer show characteristics of human wisdom.